2021
DOI: 10.1002/jhet.4355
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazole based derivatives as anticancer agents: Structure activity relationship analysis for various targets

Abstract: Benzimidazole, the benzo derivative of imidazole, is a class of bicyclic aromatic organic compound consisting of six‐membered benzene ring fused to five‐membered imidazole at 4‐ and 5‐positions of the imidazole ring. It is a vital pharmacophore of many biologically active heterocyclic compounds with a variety of pharmacological activities. Over the time, benzimidazole and its derivatives have evolved as vibrant heterocyclic systems due to their potency in a wide range of bioactive compounds like analgesics, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 151 publications
0
27
0
Order By: Relevance
“…Benzimidazole is a six-membered benzene ring fused to an imidazole ring at the 4-position and 5-position of the imidazole ring. Its derivatives exert antitumor activity mainly by inhibiting tubulin polymerization, kinase, and topoisomerase inhibitors, apoptosis inducers, and telomerase inhibitors [ 36 ]. Benzimidazole derivatives with anti-melanoma activity are presented in Figure 3 .…”
Section: The Most Potent Anti-melanoma Agent From Most Recent Studies...mentioning
confidence: 99%
“…Benzimidazole is a six-membered benzene ring fused to an imidazole ring at the 4-position and 5-position of the imidazole ring. Its derivatives exert antitumor activity mainly by inhibiting tubulin polymerization, kinase, and topoisomerase inhibitors, apoptosis inducers, and telomerase inhibitors [ 36 ]. Benzimidazole derivatives with anti-melanoma activity are presented in Figure 3 .…”
Section: The Most Potent Anti-melanoma Agent From Most Recent Studies...mentioning
confidence: 99%
“…The literature survey revealed that the benzimidazole derivatives have been extensively investigated as potential anticancer agents, and these benzimidazole derivatives exhibit anticancer effects through different mechanisms of action such as intercalating mode of action (DNA binding), nonintercalating mode of action (topoisomerases inhibition), DNA alkylation (DNA cleavage), acting on enzyme antimetabolites [DihydrofolateReductase (DHFR) inhibition], sirtuin inhibition (SIrt1 and SIrt2 inhibition), acting on structural proteins (tubulin protein inhibition), and protein kinase inhibition. …”
Section: Introductionmentioning
confidence: 99%
“…[ 31 ] Because of their importance in a variety of industries, including nutrition, cosmetics, and medicines, many scientists have studied their chemistry and have produced a wide range of benzimidazole derivatives over the last few decade. [ 32 ] Benzimidazole derivatives have been found to be effective in numerous biochemical and pharmacological activities [ 33 ] such as anti‐HIV, [ 34 ] antihistaminic, [ 35 ] antioxidant, [ 36 ] antiulcer, [ 37 ] antimalarial, [ 38 ] analgesic, [ 39 ] anti‐tubercular, [ 40 ] antiinflammatory, [ 41 ] antihypertensive, [ 42 ] antimicrobial, [ 43 ] antiprotozoal, [ 44 ] antihelmintic, [ 45 ] anticancer, [ 46 ] antidiabetic, [ 47 ] antihypertensive, [ 48 ] DNA binding, [ 49 ] and antifungal [ 50 ] activities.…”
Section: Introductionmentioning
confidence: 99%